Răspuns :
[tex]x+0*y+5=0 \\ x+5=0 \\ x=-5[/tex]
[tex]0*x-y+4=0 \\ -y+4=0 \\ -y=-4|*(-1) \\ y=4[/tex]
[tex]0*x-y+4=0 \\ -y+4=0 \\ -y=-4|*(-1) \\ y=4[/tex]
a) 0*y este bineinteles 0
x+0+5=0
x+5=0 => x=-5
b) 0*x este 0
0-y+4=0 => 0-y=-4 => y=0-(-4)= 0+4=4
Daca te-am ajutat, nu ezita sa imi oferi o inimioara si o coroana <3 O zi placuta in continuare!
x+0+5=0
x+5=0 => x=-5
b) 0*x este 0
0-y+4=0 => 0-y=-4 => y=0-(-4)= 0+4=4
Daca te-am ajutat, nu ezita sa imi oferi o inimioara si o coroana <3 O zi placuta in continuare!